2018
DOI: 10.1155/2018/7279036
|View full text |Cite
|
Sign up to set email alerts
|

Possible Enzymatic Downregulation of the Natriuretic Peptide System in Patients with Reduced Systolic Function and Heart Failure: A Pilot Study

Abstract: Background In patients with reduced systolic function, the natriuretic peptide system affects heart failure (HF) progression, but the expression of key activating (corin) and degrading enzymes (neprilysin) is not well understood. Methods and Results This pilot study (n=48) compared plasma levels of corin, neprilysin, ANP, BNP, and cGMP in control patients with normal ejection fractions (mean EF 63 ± 3%) versus patients with systolic dysfunction, with (EF 24 ± 8%) and without (EF 27 ± 7%) decompensated HF (dHF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 17 publications
1
41
0
1
Order By: Relevance
“…Converging lines of evidence from clinical and translational studies have shown that genetic abnormalities and reduction in corin cardiac expression level negatively affect DCM and HFrEF outcomes. Cardiac transcripts and circulating levels of corin are depressed in patients and translational animal models with DCM and HFrEF [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]35,36,51], and are pathologically modulated in DCM before the onset of edema and other clinical signs and symptoms of HFrEF [22,23]. In a translationally relevant mouse model of DCM-HFrEF with reduced cardiac and plasma corin levels, we reported that genetic restoration of cardiac-specific catalytically active, native corin improved systolic function, reduced myocardial fibrosis, decreased edema, and prolonged survival [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Converging lines of evidence from clinical and translational studies have shown that genetic abnormalities and reduction in corin cardiac expression level negatively affect DCM and HFrEF outcomes. Cardiac transcripts and circulating levels of corin are depressed in patients and translational animal models with DCM and HFrEF [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]35,36,51], and are pathologically modulated in DCM before the onset of edema and other clinical signs and symptoms of HFrEF [22,23]. In a translationally relevant mouse model of DCM-HFrEF with reduced cardiac and plasma corin levels, we reported that genetic restoration of cardiac-specific catalytically active, native corin improved systolic function, reduced myocardial fibrosis, decreased edema, and prolonged survival [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence in humans and experimental models suggests that corin, a cardiac transmembrane II serine protease, plays diagnostic, prognostic, and protective roles in DCM and HFrEF development [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Cardiac corin is co-expressed with pro-atrial natriuretic peptide (pro-ANP) and localized on the cardiomyocyte surface [25,26], where it cleaves/activates secreted pro-ANP generating biologically active ANP peptides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, key questions remain unanswered to understand the physical meaning of these measurements in patients. In HF, levels of cardiac and circulating (plasma) corin, are consistently decreased [ 4 , 7 ] and the magnitude of corin reduction is correlated with the severity of heart dysfunction [ 9 , 39 ]. However, whether lower circulating corin was accompanied with decreased cardiac corin expression in case of stroke or preeclampsia is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Неблагоприятным последствием легочной гипертензии, в контексте ее аритмогенной активности, будет расширение правых отделов сердца и изменение архитектоники их миокарда. Доказана связь между возрастанием диаметра правого желудочка у лиц с ХОБЛ и наличием у них ФП [30]. Следовательно, можно полагать, что размер правых камер сердца несет диагностическую значимость в качестве фактора возникновения ФП у больных ХОБЛ.…”
Section: гемодинамические нарушения с последующим развитием легочной unclassified